Families with Adolescents Bridging the Gaps Between Theory, Research, and Practice - Gavazzi, Stephen M.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Despite their flocking to social networking sites in unprecedented numbers, research confirms that adolescents continue to be influenced primarily by their families rather than their peers and other social contexts. Consequently, the family unit remains a vital setting for understanding and intervening with youth. Synthesizing important findings from the literature on family science and such related fields as psychology, sociology, social work, and public health, Families with Adolescents focuses a unique panoramic lens on the study of adolescent development. This concise volume offers a clear blueprint for more consistently improved practice, emphasizing family process and structure instead of individual developmental stages. Its chapters deftly summarize the recent knowledge base across the mental health and social services disciplines, illustrating family concerns and theoretical perspectives coupled with real-world vignettes and making cogent use of family assessment measures. Featured topics include: Central concepts of family development, family systems, ecological, attachment, and social learning theories in relation to families with adolescents. Impact of the family on adolescent behavior, education, and mental health outcomes. Selected studies on parenting behaviors, conflict resolution, and other major aspects of families with adolescents. Application topics in family-based intervention and prevention programs. Integrating theory, research, and applications to create a (3z(Btriple threat(3y (Bmodel. Families with Adolescents is an essential resource for researchers and graduate students as well as mental health therapists in clinical child and developmental psychology, family studies, human development, sociology, social work, and education.s
Part 1: Introduction and Overview of Theoretical, Research, and Application Topics -- Introduction -- Overview of Theory, Research, and Application Topics -- Part 2: Theorizing About Families with Adolescents -- Family Development Theory -- Family Systems Theory -- Ecological Theory -- Attachment Theory -- Social Learning Theory -- Part 3: Research on Families with Adolescents -- Research on the Parent-Adolescent Dyad -- Polyadic Research on Families with Adolescents -- The Family$1 (Bs Impact on Adolescent Outcomes -- Part 4: Application Topics Concerning Families with Adolescents -- Family Therapy and other Family Intervention-Based Efforts -- Family Prevention Programs -- Part 5: Summary and Future Directions -- Outlook on Theoretical, Research, and Application Efforts to Date -- The Need to Integrate Theory, Research, and Application Efforts -- References.s
Keywords: Philosophy (General).; Social work; Sociology; Applied psychology; Developmental psychology; Psychology; Child and School Psychology; Developmental Psychology; Psychotherapy and Counseling; Sociology; Social Work; Sociology of Education